Study and Analysis of Road Widening and Strengthening - Gireesh Babu, Sunil Biradar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The high growth number of vehicles will increase the movement and the use of transport infrastructure. Road widening is one of the actions that can be used as the solution. However, this solution also increases the traffic performance.This is because people will switch to use the nee road widened because they believe this road can accommodate the existing traffic volume. For finding out the effects of road widening towards the increasing of traffic performance and road capacity, it is necessary to conduct a research and an analysis.The Road network of any city is its lifeline, and the evaluation of their performance is very necessary for future traffic planning, design, operation, and maintenance etc.Traffic flow is most cities of India is mixed traffic characteristics and the traffic congestion id the common problem in most major cities in India.In this project on "widening and strengthening of the road" and aimsto widen the roads in Ranga Reddy district of Telangana. Under this project, single lane roads are modified as double lane roads. The project includes the improvement of roads connecting a particular area. Total length of the road is 18km.